Identification of Local Rice Genotypes from Deli Serdang, North Sumatera, Indonesia to Drought Stress Condition - Irawati Chaniago; Noverina Chaniago; Irfan Suliansyah; Nalwida Rozen (Green Engineering Society, 2021)
Regency of Deli Serdang in the Province of Sumatera Utara has high diversity of landrace rice that has adapted to various climatic and edaphic condition including drought. Studies on various local rice genotypes tolerant to drought is of important to be carried out. This will help plant breeders with germplasms for future breeding program. Polyethylene glycol (PEG) is a water-soluble compound with high osmotic pressure and unlikely to have specific interaction with biological chemicals. With these properties, PEG is often be used in studies of plant response to drought stress. The experiment reported here was aimed at determining rice genotypes, local to Regency of Deli Serdang, tolerant to drought. The experiment was carried out at Laboratory of Physiology and Glass House of Faculty of Agriculture, Universitas Islam Sumatera Utara, Medan from February to April 2020. A two-way factorial experiment was assigned in a completely randomized design (CRD) with 3 replicates. The first factor was 23 local rice genotypes plus 4 genotypes tolerant to drought and the second factor was the concentration of PEG 6000 i. e 0 and 20% (w/v). Observations included percent of germination, plant height, length and number of roots protruding from paraffin-wax layer, leaf chlorophyll content, seedling fresh and dry weight, index of tolerance, probability of resistance, and proline content. Data were analyzed with analysis of variance and mean separation of DNMRT at 5%. Results demonstrated that 6 local rice genotypes, Gemuruh, Ramos Merah, Arias, Sialus, Silayur, and Sirabut were resistant to drought stress under the experimental condition.